2019
DOI: 10.3906/kim-1808-51
|View full text |Cite
|
Sign up to set email alerts
|

Improving the mechanical and thermal properties of chlorinated poly(vinylchloride) by incorporating modified CaCO3nanoparticles as a filler

Abstract: Chlorinated poly(vinyl chloride) (CPVC)/calcium carbonate nanocomposites were successfully prepared by the incorporation of calcium carbonate (CaCO 3) nanoparticles into the CPVC matrix. The compatibility between the two phases was obtained by surface modification of the CaCO 3 nanoparticles with stearic acid, leading to improved material performance. The effects of the addition of different amounts of CaCO 3 nanoparticles to the CPVC on the thermal, mechanical, and morphological characteristics of the CPVC/Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Calcium carbonate is one of the most widely used fillers for the PVC leather industry [ 14 16 ], conventionally CaCO 3 has been employed to minimize its cost and enhance its melting viscosity, and mildly increase the modulus of the final product due to its small surface area and undesirable geometrical aspects [ 17 ]. However, some mechanical properties remained constant or, in some circumstances, declined [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium carbonate is one of the most widely used fillers for the PVC leather industry [ 14 16 ], conventionally CaCO 3 has been employed to minimize its cost and enhance its melting viscosity, and mildly increase the modulus of the final product due to its small surface area and undesirable geometrical aspects [ 17 ]. However, some mechanical properties remained constant or, in some circumstances, declined [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that CaCO 3 particle size and content have a significant effect on the morphological structure [ 17 , 21 , 22 ], the thermal characteristics [ 16 , 23 , 30 ], and the physical properties of the PVC products [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies examining the mechanical properties of materials and making mechanical improvements are as follows. In one of these studies; by preparing nanocomposites containing calcium carbonate, the thermal, mechanical and morphological properties of these composites were investigated [5]. As a result of the examination, the researchers concluded that the CaCO3 ratio was 3.75%, where the nanocomposite used showed the highest impact and tensile strength.…”
Section: Introductionmentioning
confidence: 99%